Pandangan Teodisi Murtadha Muthahhari sebagai Jawaban Terhadap Problem of Evil (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
Abstract The problem of evil is one of the most powerful weapons that atheists always use to attack the existence of God taught by religions. The presence of the evil in life is a philosophical issue that challenges the beliefs of religious communities to reconcile the existence of God with the fact that there is evil in life. The theistic conception of God has raised a very difficult problem because God with all His greatness, should be able to create a world life that is far better than it is today. This problem of evil has challenged theologians as well as philosophers and discussed and led to serious and lengthy discussions to provide satisfactory answers and do not offend the justice of God. Theologians and philosophers want to show that the existence of evil and suffering are not contradictory, in other words consistent with the existence of God. Arguments that try to address this problem of ugliness are called theodicy. One of the philosophers as well as theologians who participates in discussing and contributing his theodicy thoughts in answering the problem of ugliness and its relation to divine justice is Murtadha Mutahhari. This article aims to describe Murtadha Mutahhari's theodicy views as an answer to the problem of evil. This study uses a qualitative method with a descriptive approach. As a result, this research concludes several things; first, evil is non-existence; secondly, evil is relative; third, in a holistic view, evil has benefits that give meaning to this life. Keyword : Theodicy, Problem of Evil, Murtadha Muthahhari